2015
DOI: 10.1007/s00128-015-1621-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphate Addition on Cadmium Precipitation and Adsorption in Contaminated Arable Soil with a Low Concentration of Cadmium

Abstract: The objectives of this study were to determine (1) the phosphorus (P) level required to induce cadmium (Cd) precipitation in a contaminated arable soil with low concentrations of Cd and (2) the primary mechanism of Cd immobilization at different P levels. Phosphorus was added at levels of 0 800, 1600, and 16,000 mg P kg(-1) to a soil containing 5.57 mg Cd kg(-1). The concentration of 1 M NH4OAc extractable Cd decreased significantly with P levels up to 1600 mg kg(-1) due to an increase in soil pH and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The study area is a forest with vigorous vegetation. The Cd and As in the soil absorbed by plants were returned to the surface soil in the form of litter, which provides a source for the accumulation of Cd and As on the soil’s surface [41].…”
Section: Resultsmentioning
confidence: 99%
“…The study area is a forest with vigorous vegetation. The Cd and As in the soil absorbed by plants were returned to the surface soil in the form of litter, which provides a source for the accumulation of Cd and As on the soil’s surface [41].…”
Section: Resultsmentioning
confidence: 99%
“…1a, Fig. 3;Hong et al 2014;Kim et al 2015). Hong et al (2014) also found that the addition of high amount of P fertilizer significantly increased the residual Cd fraction in Cd-contaminated soil.…”
Section: Effects Of Biochar and P Fertilizer On Soil CD Fractionmentioning
confidence: 77%
“…On the other hand, the abundance of available P in soil provided by application of biochar and P fertilizer creates conditions for the occurrence of precipitation and promotes the conversion of carbonate and organic Cd forms to residual Cd fraction (Fig. 3; Chen et al 2020;Hamid et al 2019;Kim et al 2015). And the alkaline feature of biochar was the necessary condition for stable precipitation formation (Fig.…”
Section: Effects Of Biochar and P Fertilizer On Soil CD Fractionmentioning
confidence: 99%
“…Previously, it has been reported that cadmium is capable of forming complexes with nucleotides, possibly through the interaction with the phosphate groups (Sigel et al ., 2013). In addition, phosphate amendments have been shown to be effective in immobilizing cadmium in soils by enhancing cadmium precipitation as Cd 3 (PO 4 ) 2 (Hong et al ., 2014; Kim et al ., 2015). Based on these findings, it is likely that phosphate is involved in cadmium detoxification via its role in reducing cadmium bioavailability.…”
Section: Introductionmentioning
confidence: 99%